Implementasi Rest Api Web Service dalam Membangun Aplikasi Multiplatform untuk Usaha Jasa - Romi Choirudin; Ahmat Adil (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2019)
The development of tourism activities on the island of Lombok has caused many types of professions to be occupied or utilized by the community, especially those who are services. With the technological advancements, people need various kinds of facilities in carrying out their businesses and activities. One of them is in looking for artisan services including price or service fees, material prices and so on. Multiplatform applications (more than one platform) can make it easy for users to choose the platform to be used. With web service architecture as a computational entity that can be accessed through the internet and intranet networks and certain protocol standards in the platform and interface of an independent programming language. In conducting research, the system development method used by the author is the waterfall method. Waterfall method is a systematic and sequential method of software development that starts at the level and progress of the system up to the analysis, design, code (implementation), test (testing), and maintenance. The application that was built has been tested to several builders. As well as from the results of testing the artisan respondents have a very agreeable answer of 51.4%, because 51.4% is the highest result in the response to the response of the answer, it can be concluded that the application has met the needs of the mason